Effect of bisphenol-A on the structures and properties of phthalonitrile-based resin containing benzoxazine - M. Z. Xu; K. Jia; X. B. Liu (eXPRESS Polymer Letters, 2015)
Phthalonitrile and benzoxazine have been considered as high-performance materials in the field of heterocyclic chemistry. The polymerization of phthalonitrile and benzoxazine accelerated by active phenolic hydroxyl has attracted wide interests. In this work, self-promoted polymerization behavior and processability of phthalonitrile containing benzoxazine (BA-ph) with bisphenol-A (BPA) were investigated. Results revealed that BA-ph/BPA exhibited representative doublestage curing behaviors corresponding to the ring-opening polymerization of benzoxazine rings and ring-formation polymerization of nitrile groups. Compared with that of BA-ph, processability of BA-ph/BPA was improved and could be tuned by varying BPA contents, processing temperature and time. Then BA-ph/BPA/glass fiber (GF) composite laminates were prepared. In comparison with that of BA-ph/GF laminates (542 MPa and 25.8 GPa), the flexural strength and modulus were up to 789 MPa and 23.6 GPa, respectively. Moreover, double Tgs were observed at temperature around 200~300°C and 300~380°C, indicating microphase separation during the polymerization of oxazine rings and nitrile groups, confirmed by the scanning electron microscopic (SEM) images. Thermal stabilities demonstrated that all BA-ph/BPA/GF composites exhibited high T10% up to 510°C. The systematic study of BA-ph/BPA system could enrich our knowledge on phthalonitrile-based resins in industrial applications, especially in the areas which require excellent mechanical properties and high temperature resistance.